UTILIZATION OF PROCESSING TEMPEH WASTE INTO HIGH PROTEIN FLOUR AS AN EFFORT TO PREVENT STUNTING IN KALIJAGA - Vianty Mutya Sari; Lairie Lairie; yahlini Gita Fitri; Syarifah Nur Intan; Tia Yulianti; Rizki Amalia; Ria Yulianti Triwahyuningsih; Rahma Amalia Sudrajat; Rinda Tri Wahyuni; Syafira Fatia; Siti Laela Sari Ningsih (Ann Publisher, 2026)
Background. Stunting is a global health problem that affects children's growth and development, particularly in cognitive, motor, and emotional domains. In RW 04 Kalijaga Village, the problem of stunting is still a major concern because of the high prevalence of children with growth disorders compared to other areas. The main factors contributing to stunting in this region include a lack of parental education on proper parenting, a low understanding of balanced nutrition, and limited access to health services. Aims. This study aims to identify and describe the factors that affect the incidence of stunting, as well as interventions to improve parents' understanding of how to support optimal child growth and development. Methods. The method involves observing children's growth and development using emotional, auditory, fine motor, and gross motor parameters, as well as parenting education delivered through digital media and direct interaction. Result. The outputs targeted in this study include increasing public understanding of child parenting, increasing awareness of the importance of monitoring children's growth and development from an early age, and the creation of educational media in the form of animated videos and comics that can be accessed by the wider community. In addition, this research contributes to mapping stunting incidence in RW 04 as a basis for public health policy-making. TKT (Technology Readiness Level) of this study is at levels 4-5, where interventions have been tested on a community scale with an education-based and digitalization-based approach. Implementation. The next step is to apply the results of this research at a broader scale to have a significant impact on efforts to combat stunting across regions.